Energy and exergy analysis of parallel flow double effect H2O-[mmim][DMP] absorption refrigeration system for solar powered district cooling - M. Salim Ferwati (8407596) (2021)
Solar thermal energy-driven double effect absorption refrigeration system (DE-ARS) for district cooling in smart cities is an efficient, and sustainable alternative for centralized air conditioning and concurrently harnesses low-grade solar energy. This work investigates ionic liquid based H2O-[mmim][DMP] mixture as an alternative working fluid to overcome the drawback of H2O–LiBr driven DE-ARS. The thermodynamic properties of H2O-[mmim][DMP] mixture is evaluated using the excess Gibbs free energy model. Performance modeling and simulation of DE-ARS is based on both energy and exergy analysis by applying the first and second laws of thermodynamic. The performance, and solution circulation ratio of parallel flow DE-ARS is assessed and optimized under various temperatures and solution distribution ratios. In comparison to the conventional H2O–LiBr, the proposed H2O-[mmim][DMP] working fluid achieves 5.22% and 4.95% improvement in COP and ECOP, respectively at Th/Te/Ta/Tc of 140/5/30/30°C . An optimization of generator temperature to achieve maximum COP and ECOP is performed for a wide range of evaporation temperature from 5 to 20°C and Ta/Tc from 30 to 40°C. An optimization of H2O-[mmim][DMP] mixture driven DE-ARS reveals the uppermost COPmax and ECOPmax of 1.81 and 0.69 for Te of 20°C and TaTc=30°C. Other Information Published in: Case Studies in Thermal Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.csite.2021.101382